The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 IEEE/ACM 39th International Conference on Software Engineering: Software Engineering in Practice Track (ICSE-SEIP) 2017
DOI: 10.1109/icse-seip.2017.25
|View full text |Cite
|
Sign up to set email alerts
|

Scaling agile development in mechatronic organizations - a comparative case study

Abstract: Agile software development principles enable companies to successfully and quickly deliver software by meeting their customers' expectations while focusing on high quality. Many companies working with pure software systems have adopted these principles, but implementing them in companies dealing with non-pure software products is challenging.We identified a set of goals and practices to support large-scale agile development in companies that develop software-intense mechatronic systems.We used an inductive app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 13 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…The goal of this paper was to collect more evidence about impact factors for scaling agile software development processes inside companies, to better understand practices that work best in a given context . By means of a review of studies about large‐scale agile in organizations, we identified practices, challenges, and success factors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The goal of this paper was to collect more evidence about impact factors for scaling agile software development processes inside companies, to better understand practices that work best in a given context . By means of a review of studies about large‐scale agile in organizations, we identified practices, challenges, and success factors.…”
Section: Resultsmentioning
confidence: 99%
“…Agile software development is very popular nowadays, as its application in many different contexts shows . However, traditional agile methods were designed with a single team in mind and were not meant to face scalability challenges .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most USCRC researchers do not work in software. Although there are software-related aspects to control, mechanics, and other areas, researchers need to manage many projects outside software in a fundamentally different way (Eklund and Berger 2017). In our experience, we observed that quick turnaround times in fabrication of improved versions of prototypes can make the deliverables well-suited for early feedback from BUs.…”
Section: Software Non-software and Hybrid Systems And Skillsetsmentioning
confidence: 90%